A Synthesis of Animation and Jazz in Begone Dull Care - Pinson, Heather (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2017)
In 1949 filmmakers Norman McLaren and Evelyn Lambart created the seven-minute, forty-eight-second, animated short Begone Dull Care, filled with abstract images moving in time to the music of the Oscar Peterson Trio. In this three-movement film, McLaren and Lambart use the improvisatory nature of jazz to establish a narrative, allowing the animated shapes to respond and react to the music itself. This article addresses the collaboration between artists and musicians to create such an influential piece and examines the interdisciplinary relationship between music and animation in Begone Dull Care.